1992
DOI: 10.1177/0306624x9203600106
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Criminal Behavior Revisited

Abstract: The authors review some statistical studies regarding the relationships between mental illness and criminal behavior prior to, and following, the deinstitutionalization period. This review supports the common opinion that since deinstitutionalization the jails of the United States house great numbers of the mentally ill. Even though mental illness, per se, is not synonymous with violence-prone behavior, the percentage of mentally ill in the jails is growing. Their offenses usually consist of misdemeanors, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Consistent with other studies, most cases in the current study were males [ 8 , 12 ] and previous contact with psychiatric services was found in 58% of cases [ 13 , 14 ]. However, the current study showed that prediction of danger in the murder and robbery groups is questionable, as the last contact of both groups with psychiatric services was significantly shorter than other groups.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies, most cases in the current study were males [ 8 , 12 ] and previous contact with psychiatric services was found in 58% of cases [ 13 , 14 ]. However, the current study showed that prediction of danger in the murder and robbery groups is questionable, as the last contact of both groups with psychiatric services was significantly shorter than other groups.…”
Section: Discussionsupporting
confidence: 93%
“…Second, time-series studies produced weak evidence of trans-institutionalization (for supportive evidence, see Palermo, Gumz, & Liska, 1992; for non-supportive evidence, see Grabosky, 1980; Inverarity & Grattet, 1989). Drawing on aggregate national data from 1926 to 1987, Palermo et al (1992) found a significant and negative (bivariate) correlation between mental hospital and jail populations. However, multivariate studies reported that there is no evidence of trade-offs.…”
Section: Empirical Findings Of Deinstitutionalization and Imprisonmentmentioning
confidence: 99%
“…Although there is adequate literature on clinical outcomes, service-systems designs, and ethics for staff who work with incarcerated mentally ill offenders (Alexander, 1997;Palermo, Gumz, & Liska, 1992;Pollock, 1997; Rice, 1997;Souryal, 1998), there is not much about the influence of unconscious beliefs and values on prison treatment operations. Part of the reason for this is that there are few measurement instruments with adequate scope, reliability, and relevance to describe closely held beliefs and how they translate into behaviors in a complex environment (Roskin, Carsen, Rabiner, & Marell, 1988).…”
Section: Theoretical Frameworkmentioning
confidence: 99%